Diterpenoids caryopterisoids D - Q and iridoid glucoside derivatives caryopterisides F - H from Caryopteris glutinosa. (December 2020) - Zhang, Xuejian; Peng, Ting; Shi, Xiaoke; Fang, Dongmei; Tang, Lin; Chen, Fang; Wang, Fei; Zhang, Guolin; Luo, Yinggang
Abstract: Fourteen undescribed diterpenoids caryopterisoids D - Q, three undescribed iridoid glucoside derivatives caryopterisides F - H, and 8 known diterpenoids were isolated from the 95% aqueous ethanolic extract of Caryopteris glutinosa. Their structures were elucidated on the basis of spectroscopic data analysis and chemical derivation studies. The structure and absolute conﬁguration of caryopterisoid D were confirmed by X-ray crystallographic analysis. Caryopterisoids K and R, royleanone, 6α-hydroxydemethylcryptojaponol, and teuvincenone E were shown to reduce the biosynthesis of estrogen E2 with IC50 values from 0.25 to 3.06 μM in cell-based estrogen biosynthesis assays system. Graphical abstract: Image 1 Highlights: Seventeen unprecedented natural products were identified from Caryopteris glutinosa. Caryopterisoids D - Q (1 – 14 ) are diterpenoids and diterpenoid derivatives. Caryopterisides F – H (15 - 17 ) are iridoid glucosides modified with vanillic acid. The absolute conﬁgurations of 1 were confirmed by X-ray crystallographic analysis. Compounds 8, 14, 19, 21, and 25 reduce E2 biosynthesis with IC50 = 0.25–3.06 μM.